Cetacean distribution and relative abundance in Colombia’s Pacific EEZ from survey cruises and platforms of opportunity - Palacios, Daniel M.; Herrera, Julio C.; Gerrodette, Tim; Garcia, Carolina; Soler , German A.; Avila , Isabel C.; Bessudo, Sandra; Hernandez, Elizabeth; Trujillo, Fernando; Forez-Gonzalez, Lilian; Kerr , Iain (J. Cetacean Res. Manage., 2023)
Cetacean sighting data collected under various programmes in Colombian Pacific waters were collated with the goal of assessing the distribution and abundance patterns of all species occurring in the exclusive economic zone (EEZ). Distribution maps are presented for 19 species and one genus based on 603 sightings collected between 1986 and 2008. Ordered by sighting frequency, these species were: humpback whale (Megaptera novaeangliae); striped dolphin (Stenella coeruleoalba); common bottlenose dolphin (Tursiops truncatus); pantropical spotted dolphin (Stenella attenuata); common dolphin (Delphinus delphis); Risso’s dolphin (Grampus griseus); sperm whale (Physeter macrocephalus); rough-toothed dolphin (Steno bredanensis); short-finned pilot whale (Globicephala macrorhynchus); mesoplodont whales (Mesoplodon spp.); Cuvier’s beaked whale (Ziphius cavirostris); melon-headed whale (Peponocephala electra); false killer whale (Pseudorca crassidens); killer whale (Orcinus orca); spinner dolphin (Stenella longirostris); dwarf sperm whale (Kogia sima); Bryde’s whale (Balaenoptera edeni); pygmy killer whale (Feresa attenuata); minke whale (Balaenoptera acutorostrata) and fin whale (Balaenoptera physalus). Concentrations of sightings were observed in three geographic areas: (1) the continental shelf (depths <200m) and the contiguous continental slope (200–2,000m); (2) over the Malpelo Ridge, an offshore bathymetric feature and (3) the northeast corner of the EEZ between Golfo de Cupica and the border with Panamá, although we do not rule out that these patterns could be an artefact of non-random effort. In inshore waters, the most frequently seen species were pantropical spotted dolphin, common bottlenose dolphin and humpback whale. For several of the data sets we provide encounter rates as indices of relative abundance, but urge caution in their interpretation because of methodological limitations and because several factors that affect sightability could not be accounted for in these estimates. Our results provide useful information for ongoing regional research and conservation initiatives aimed at determining occurrence, population status and connectivity within adjacent EEZs in the eastern tropical Pacific. Suggested research priorities include conducting dedicated surveys designed for estimating abundance and monitoring trends throughout the EEZ and focused studies in areas of special interest like the continental shelf, the Malpelo Ridge and the vicinity of Cupica and Cabo Marzo. More research is also needed in terms of quantifying the sources and impact of anthropogenic mortality on population size. Studies characterising genetic diversity and stock discreteness in coastal species (pantropical spotted dolphin and common bottlenose dolphin) would help inform local management strategies.